Knowledge and Attitudes of Nurses About Pain Management in Neonates in the Perinatology Room and PICU / NICU - Mariyam Mariyam; Ika Nur Hidayati; Dera Alfiyanti (Universitas Muhammadiyah Semarang, 2019)
Background: Nurse’s knowledge and attitude toward neonatal pain management is very beneficial for the accuracy in giving neonatal intervention. Therefore, nurse should possess the sufficient knowledge and attitude to give the proper pain intervention, so that it will be effective to treat the neonatal pain. Objective: This study aims to find out the knowledge and attitude of nurse toward neonatal pain management at Perinatology and PICU/NICU rooms of Hospital in Semarang. Methodology: It was a descriptive study using total sampling technique which employed 50 nurses as the respondents. Resulth: From the research, it was drawn that most of the respondents’ knowledge were excellent (58.0%) and the respondents’ attitude were mostly adequate (68.0%). Based on the result, the nurses of PICU/NICU and Perinatology rooms are expected to improve the attitude toward neonatal pain management as the pain will significantly lessen by the proper attitude.